The Nitrogen Cycle in an Epeiric Sea in the Core of Gondwana Supercontinent: A Study on the Ediacaran-Cambrian Bambuí Group, East-central Brazil - Fraga-Ferreira, Paula Luiza; Ader, Magali; Caetano-Filho, Sérgio; Sansjofre, Pierre; Paula-Santos, Gustavo Macedo; Babinski, Marly; Guacaneme, Cristian; Bedoya-Rueda, Carolina; Rojas, Virginia; Reis, Humberto L. S.; Kuchenbecker, Matheus; Trindade, Ricardo I. F. (Frontiers in Earth Science, 2021)
The Ediacaran-Cambrian transition is marked by the diversification of metazoans in the marine realm. However, this is not recorded by the Ediacaran-Cambrian Bambuí Group of the São Francisco basin, Brazil. Containing the sedimentary record of a partially confined foreland basin system, the Bambuí strata bear rare metazoan remnants and a major carbon isotope positive excursion decoupled from the global record. This has been explained by changes in the paleogeography of the basin, which became a restricted epicontinental sea in the core of the Gondwana supercontinent, promoting episodes of shallow water anoxia. Here, we report new δ15Nbulk data from the two lowermost 2nd-order transgressive-regressive sequences of the Bambuí Group. The results show a rise of δ15N values from +2‰ to +5‰ in the transgressive system tract of the basal sequence, which was deposited when the basin was connected to other marginal seas. Such excursion is interpreted as an oxygenation event in the Bambuí sea. Above, in the regressive systems tract, δ15N values vary from +2‰ to +5‰, pointing to instabilities in the N-cyle that are concomitant with the onset of basin restrictions, higher sedimentary supply/accommodation ratios, and the episodic anoxia. In the transgressive systems tract, the δ15N values stabilise at ~+3.5‰, pointing to the establishment of an appreciable nitrate pool in shallow waters in spite of the basin full restriction as marked by the onset of a positive carbon isotope excursion. In sum, our data show that the N-cycle and its fluctuations were associated with variations in sedimentary supply/accommodation ratios induced by tectonically-related paleogeographic changes. The instability of the N-cycle and redox conditions plus the scarcity of nitrate along regression episodes might have hindered the development of early benthic metazoans within the Bambuí seawater and probably within other epicontinental seas during the late Ediacaran-Cambrian transition.